Strategi Peningkatan Mutu Produk Olahan Ikan Tangkap di Kecamatan Sungai Kakap - Ayuni Ayuni; Maswadi Maswadi; Anita Suharyani; Marisi Aritonang; Wanti Fitrianti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Kubu Raya Regency is the fourth largest producer of processed fish in West Kalimantan. Business actors generally pay less attention to things that will affect product quality. Processed fish products have quality problems such as decreased quality during storage, microbial contamination during the salting process, use of chemicals, unpleasant odors, and deviations from industry standards. Business actors who can produce highly competitive products have three criteria: products that are available regularly and continuously, products of excellent and uniform quality, and widely available products. Improving product quality products is an excellent way to maintain customer loyalty, have the resilience to compete, and build sustainable growth and profits. This study aims to formulate a quality strategy for processed fishery products in Sungai Kakap District. The study was conducted in April 2024, with ten respondents of processed fish product business actors. The variables used are quality control indicators consisting of performance, completeness, reliability, durability, and service capabilities, which are then analyzed using a SWOT matrix. The study results show that processed fish product business actors in Sungai Kakap District are in quadrant two. Quadrant two shows that business actors can take advantage of existing external opportunities to overcome their internal weaknesses. The strategies developed in this quadrant focus on ways to improve internal weaknesses by taking advantage of opportunities in the external environment to ensure that business actors can improve their overall position and be better prepared to face future challenges.